2014
DOI: 10.1248/bpb.b13-00508
|View full text |Cite
|
Sign up to set email alerts
|

Transposition of the Zorro2 Retrotransposon Is Activated by Miconazole in <i>Candida albicans</i>

Abstract: Zorro2 is a member of a non-long terminal repeat (LTR) retrotransposon family in Candida albicans, but as yet no clear evidence has been provided to establish either transcription or transposition activity for Zorro2. In this study, the relative expression changes of two open reading frames in Zorro2, ORF19.7274 and ORF19.7275, were examined in response to miconazole (MCZ), and were found to be increased by this treatment. As well, the copy number and the transcripts of Zorro2 in MCZ-induced resistant daughter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…ROS also act as second-messenger signaling molecules, regulating multiple cell functions, including autophagy and apoptosis (42)(43)(44). The induction of intracellular oxidative stress by miconazole has been demonstrated in rat neonatal cardiomyocytes and bladder cancer cells, as well as in Candida albicans and other fungi (18,25,(45)(46)(47)(48). The present study revealed that the NAC-mediated scavenging of miconazole-induced ROS decreased the levels of LC3-II and molecular markers of ER stress.…”
Section: Discussionsupporting
confidence: 56%
“…ROS also act as second-messenger signaling molecules, regulating multiple cell functions, including autophagy and apoptosis (42)(43)(44). The induction of intracellular oxidative stress by miconazole has been demonstrated in rat neonatal cardiomyocytes and bladder cancer cells, as well as in Candida albicans and other fungi (18,25,(45)(46)(47)(48). The present study revealed that the NAC-mediated scavenging of miconazole-induced ROS decreased the levels of LC3-II and molecular markers of ER stress.…”
Section: Discussionsupporting
confidence: 56%
“…Some Zorro3 insertions are close to antifungal resistance-associated genes (Dataset S2), which may affect the expression of these genes and thus regulate antifungal susceptibility. Interestingly, the transposition of the Zorro2 retrotransposon is activated by miconazole, suggesting that these retrotransposons could be associated with antifungal resistance [37]. In C. albicans, the Zorro3 element FGR14 also regulates filamentous growth [38].…”
Section: Discussionmentioning
confidence: 99%
“…These mobile elements are affected by population density and ecological aspects, e.g., stress (Arkhipova, 2005;Johnson, 2007). For example, the non-LTR retro-transposon Zorro2 is activated by miconazole treatment (Zhu et al, 2014). Activation of these transposons leads to additional copies in the C. albicans genome.…”
Section: Genomic Adaptation and Chromosome Instability In C Albicansmentioning
confidence: 99%
“…Activation of these transposons leads to additional copies in the C. albicans genome. Although the exact role of these additional copies remains to be elucidated, Zhu et al hypothesized that these retro-transposons can patch together broken chromosome ends and provide dispersed regions of homology that facilitate chromosomal rearrangements (Dunham et al, 2002;Umezu, Hiraoka, Mori, & Maki, 2002;Zhu et al, 2014). This promotes the repair of ROS-induced DNA damage and chromosomal loss, which are consequences of miconazole treatment (Zhu et al, 2014).…”
Section: Genomic Adaptation and Chromosome Instability In C Albicansmentioning
confidence: 99%